ANTENATAL DEVELOPMENT AND ADAPTATION PERIOD OF INFANTS BORN BY MOTHERS WITH GESTATIONAL DIABETES - A.V. Kilina; M.B. Kolesnikova (Вопросы современной педиатрии, 2008)
Research goal was studying antenatal and neonatal periods of infants born by children with gestational diabetes — main group (n = 66). Comparison group was comprised of 50 children born by women with no carbohydrate metabolism abnormalities. During research obstetric, genetic and social anamnesis was studied, alongside with pregnancy, birth, infant adaptation. It was established that gestation diabetes diagnosed mostly during the second part of pregnancy had negative effect on child development, promoting the risk of diabetic emryopathy. Besides, infants of the main group showed more cases of nervous and cardiovascular dysfunctions, respiratory dysfunction syndrome, intrauterine infection, early prolonged jaundice, signs of morphofunctional immaturity. Key words: gestational diabetis, pregnancy, infants, disadaptation.